The principles of the creation of institutional repositories of the National aviation university - Іванкевич, О. В.; Вахнован, В. Ю. (Problems of Informatization and Control, 2012)
The principles of the creation of institutional repositories of the National aviation university onnogo-based software environment DSpace. The principles of formation of the content repository, which consists of materials of scientific conferences, fund-faculties and departments of the University of Comrade, annotated reports of research topics, articles, journals, students' works, dissertations and theses, patents, publications, independent researchers, etc.